Pengaruh Penerapan Service Learning terhadap Pengembangan Karakter dan Tingkat Kehadiran Remaja Naposo Bulung di HKBP Maranatha Ressort Cinta Damai - Anna Ria Silaban; Meri Kristiani Simanjuntak; Ajelina Novita Pasaribu; Sorta Taruli Martogi Simamora; Nikson Hutasoit; Justice Zeni Zari Panggabean (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This research is motivated by the low attendance and involvement of church youth in spiritual activities, as well as the weak Christian character that should be the basis of their lives. The purpose of this study is to analyze the impact of the service learning approach by IAKN Tarutung students on character development and increasing participation of Naposo Bulung youth at HKBP Maranatha Ressort Cinta Damai. This research is based on the theory of service learning (Eyler & Giles, 1999), experiential learning (Kolb, 1984), and the concept of sense of belonging (Etzioni, 1991) which emphasizes the importance of emotional involvement and critical reflection in the learning and service process. The method used is a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation, which were conducted for three months. The results of the study showed that the service learning program had a significant influence in increasing the attendance of youth from an average of 14 to 25 people per week, as well as fostering positive characters such as responsibility, discipline, and social concern. Students not only act as implementers of activities, but also as spiritual mentors and spiritual friends, who form authentic and contextual relationships with teenagers. The implications of this study confirm that service learning is an effective approach in the formation of church teenagers because it combines aspects of direct service with spiritual and academic reflection. Therefore, it is recommended that this approach be integrated more systematically into the curriculum of higher theological education and used as a model of sustainable service in the church community.